SILENCE AND WOMEN IN THE BOOK ENSAIO SOBRE A CEGUEIRA BY SARAMAGO: A FEMINIST CRITICAL APPROACH - Eméri Mokfa Matitz Celuppi, Fernanda (Revista Gênero e Interdisciplinaridade, 2023)
The present work aims to analyze the society experienced in the book, permeating the individual and collective characteristics of the human being, where a relationship between sea of milk (white as color) x blindness in darkness (traditional blindness as black) and the silencing of women through feminist criticism. Through a literary analysis as the core of the research, it is around the interpretations arising from the chosen work, since the literary analysis comes to investigate the concepts of the work, approaching psychoanalysis, whose objective is the same, but in the Literary analysis does not come to restore the author’s writing experience (let alone revisit his life), nor is it decoded overwhelming information, but following the logic of the usually complex artifacts that were obtained at a distance from the author’s body. An analysis with a feminist character is essential in the work, with a view little found about the book, the Essay on Blindness, making it interesting to carry out a new approach to it. Blindness is also, in many ways, a meditation on the different types of blindness. Where it was possible to understand and contextualize different theories.